Exploring the potential of Ilex paraguariensis coproduct: High concentration of chlorogenic acids and enhanced thermal stability - Bruna Trindade Paim; Alexandra Lizandra Gomes Rosas; Alexandre Lorini; Vania Zanella Pinto; Gisele Louro Peres; Elessandra da Rosa Zavareze; Vanessa Galli; Helen Cristina dos Santos Hackbart; Dianini Hüttner Kringel; Adriana Dillenburg Meinhart (Food Chemistry Advances, 2023)
Five tons, per hectare, of thick stems of Ilex paraguariensis are generated each harvest the external part of these (IPC) has a high concentration of chlorogenic acids but is not yet commercially exploited. Thus, it is hypothesized that the coproduct of I. paraguariensis when submitted to optimized extraction conditions will result in extracts rich in chlorogenic acids. Furthermore, optimized encapsulation by anti-solvent precipitation with zein ensures improved thermal stability. Multivariate strategies were successfully employed to obtain extraction of 10.16 g chlorogenic acids per 100 g IPC in 75 % ethanol. The mixture of IPC extract (15 mL) and zein (1.36 g) dripped (18.14 mL h−1) on the water under stirring (4 rpm) results in encapsulated with 94 % efficiency and thermal stability of up to 357.5 C. We show that it is possible to optimize the extraction of chlorogenic acids and encapsulate them in a fast and efficient way for easy industrial expansion. The high amount of chlorogenic acids and the thermal resistance of the encapsulates indicate that applications in foods exposed to heat are highly promising for the valorization of this natural resource not commercially exploited, in line with the concepts of the circular economy.